Rasio Input Energi dan Volume Reaktan pada Penerapan Ultrasonik untuk Pengolahan Biodiesel - Bambang Susilo; La Chovia Hawa; Moch. Bagus Hermanto (PERTETA, 2010)
Abstract The application of ultrasonic on biodiesel processing can increase the reaction rate and improve theconversion of plant oils into biodiesel. Factors affecting the rate of reaction on the application of ultrasonicwaves for biodiesel processing are temperature increasing, acoustic mixing, onset of cavitations andsurface tension on the micro bubble, and the formation of hot spots in the form of instantaneous pressureand high temperature on the molecular scale. The vibrator dipped into the reactants transferred mechanicalenergy which was transformed into heat, cavitations and hot spots. This research was conducted to seethe effect of the volume ratio of reactants and input energy on the rate of conversion of triglycerides intobiodiesel. The results of this study demonstrated a significant effect of the energy input to the conversion oftriglycerides into biodiesel. The greater specific input energy produced the higher conversion and the higherreaction rate. Input energy by using ultrasonic was significantly lower than the use of a mechanical stirrer. Keywords: ultrasonic, input energy, biodiesel, conversion rateDiterima: 14 Mei 2010; Disetujui: 28 September 2010